2019
DOI: 10.1002/smtd.201900583
|View full text |Cite
|
Sign up to set email alerts
|

Promising Applications of AIEgens in Animal Models

Abstract: organisms cannot be achieved from these static findings. Therefore, gaining in-depth insights into biological and physiological functions at the in vivo level is of great significance, and various imaging techniques have been explored for this purpose. [1] In addition to the clinically available magnetic resonance imaging (MRI), ultrasonic imaging, computed tomography (CT), positron emission tomography (PET), and single-photon emission computed tomography, fluorescence imaging (another distinct type of optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 351 publications
(187 reference statements)
0
22
0
Order By: Relevance
“…[ 13 ] Physical encapsulating or covalent conjugating fluorescent agents is a straight strategy to construct fluorescent imaging‐guided therapeutic systems. [ 14 ] These systems offer an opportunity to real‐time, in situ, and noninvasive monitor biological processes in cells or organisms, such as tracking drug release, tracing the processes of translocation, monitoring the excretion of therapeutic agents, and predicting treatment responses. [ 15–17 ] However, conventional organic fluorescent molecules may suffer from obvious photobleaching and severe background interference.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Physical encapsulating or covalent conjugating fluorescent agents is a straight strategy to construct fluorescent imaging‐guided therapeutic systems. [ 14 ] These systems offer an opportunity to real‐time, in situ, and noninvasive monitor biological processes in cells or organisms, such as tracking drug release, tracing the processes of translocation, monitoring the excretion of therapeutic agents, and predicting treatment responses. [ 15–17 ] However, conventional organic fluorescent molecules may suffer from obvious photobleaching and severe background interference.…”
Section: Introductionmentioning
confidence: 99%
“…[112] On basis of this fact, several ROS-responsive turn-on systems based on AIEgens have been developed for lesion-specific theranostics. [20] Abnormal level of H 2 O 2 production has proven to be closely associated with inflammation, neurodegeneration disease, diabetes, and cancer. Xia et al developed a H 2 O 2responsive theranostic turn-on probe (TT) to implement detection and treatment methods for inflammatory cells (Figure 11).…”
Section: Self-aggregation Responding To Tripeptide Gshmentioning
confidence: 99%
“…It has been reported that the expression levels of ROS, such as hydrogen peroxide (H 2 O 2 ), hydroxyl radical ( • OH), superoxide radical ( • O 2− ), hypochlorous acid (HOCl), 1 O 2 and peroxynitrite (ONOO − ), are usually much higher in pathological cells or tissues [112] . On basis of this fact, several ROS‐responsive turn‐on systems based on AIEgens have been developed for lesion‐specific theranostics [20] …”
Section: Turn‐on Theranostics Based On In Situ Aggregationmentioning
confidence: 99%
“…AIEgens have been used in many areas including optoelectronic devices, process and environment monitoring, chemical sensing, and biological imaging 58–65 . Thanks to the intrinsic merits of large Stokes shift, high brightness, good stability and biocompatibility, and turn‐on property from solution to aggregate, AIEgens have also shown great promise in the field of biomedical applications 66–73 …”
Section: Fluorescence Emission For Precise Theranosticsmentioning
confidence: 99%